Experimental and numerical study of fluid flow and heat transfer characteristics in microchannel heat sink with complex structure. (15th November 2015) - Xia, Guodong; Ma, Dandan; Zhai, Yuling; Li, Yunfei; Liu, Ran; Du, Mo
Highlights: Complex corrugation microchannels, I-type drainage way and rectangular header are adopted into heat sink. Temperature distribution curves of heater surface are drawn. Flow field explains the mechanism of heat transfer enhancement through numerical simulation. The minimum flow rate is calculated under the given maximum temperature of heater surface and given power. Microchannel heat sink with sophisticated waves provides better overall thermal performance. Abstract: Thermal management has become crucial to ensure the performance and reliability of high power chips and micro-cooling systems. The forced convective heat transfer of microchannel heat sink is a very promising method. In this paper, experiment is used to perform temperature and pressure drops and numerical simulation is used to understand and interpret the complex thermal behavior by presenting the flow field in the current complex corrugation microchannel heat sink. The comprehensive performance is evaluated by total thermal resistance and thermal enhancement factor. Compared with the equivalent rectangle microchannel heat sink, the average temperature and maximum temperature is reduced obviously and temperature distribution is more uniform albeit with higher pressure penalty for flow rates larger than 100 ml/min. It is observed that the vortex becomes bigger and moves to the middle of channel with increasing of flow rate. The enhance heat transfer mechanisms can be contributed to the heat transfer area enlarged, thermal boundary interrupted and redeveloped, chaotic advection, hot and cooling fluid better mixed by vortex formed in the reentrant cavity. The pumping power is reduced 18.99% when total thermal resistance equals to 0.446 K/W, compared with rectangle microchannel heat sink. The thermal enhancement factor can reach 1.24 for Reynolds number of 611. Therefore, complex corrugation microchannel heat sink is more economical for chip cooling system.